Russian Tea Trade in Hankou during Second Half of 19th Century: Production of Brick Tea - I. R. Khamzin; R. T. Ganiev (Научный диалог, 2023)
This article addresses the issue of producing the socalled “brick tea” in China at Russian factories during the second half of the 19th century. Compressed teas constituted the second largest group after looseleaf teas highlighted in prerevolutionary Russian literature, sources, and statistics among Chinese teas exported to the Russian market. The study explores aspects of brick tea production that have been least covered in previous historiography. These include issues related to the procurement of raw materials for further pressing at Russian factories, pricing strategies for this product, and the accompanying competition. The experience of utilizing hydraulic presses for more efficient tea production, as well as the dynamics and volumes of brick tea production, are examined. The research revealed that in the latter half of the 19th century, Russian entrepreneurs in Hankou successfully organized the process of fabricating pressed teas, thereby contributing to the strengthening and further development of Russo-Chinese relations. Documents from central Russian archives were utilized in this study, enabling the unveiling of many previously unexplored aspects of the history of Russo-Chinese trade.